Potensi Pemanfaatan Tanaman Thypa sp dan Cyperus sp dalam Proses Remediasi Air Asam Tambang dengan Sistem Rawa Buatan - Apong Sandrawati; Darmawan Darmawan; Dyah Tj. Suryaningtyas; Gunawan Djadjakirana (Soilrens, 2018)
Acid mine drainage (AMD) is the main problem in open pit mining due to extremely low pH and high solubility of metals. Metal solubility can be reduced biochemically in an anaerobic condition. This research was aimed to design and test artificial wetland system constructed. The artificial wetland has been constructed, it contains with two organic wall, two growing pond, and one collecting pond, each component bounded by dike. Organic wall was placed next to growing pond that planted by Typha sp and Cyperus sp. Collecting pond was planted by Eichornia crassipes. Iron and Manganese were accumulated in the root of each plant. Cyperus sp has a fibril type while Typha sp has rhizome type. The fine roots such as root of Cyperus sp could accumulation Fe higher than a rhizome roots such as root of Typha sp. Productivity of biomass was 31,38 ton/ha for Eichornia crassipes, 17,11 ton/ha for Typha sp, and 16,67 ton/ha for Cyperus sp. Eichornia crassipes has a higher biomass than other plants, but the size of this plant become smaller, it because the lack of nutrient in collecting ponds. Cyperus sp seems more prospective, this plant has better of growth rate than other plants.